Intersecting Dynamics: Migration, State Control and Urban Expansion in Shenzhen’s Urban Villages - Wang, Qingzheng (International Journal of Social Sciences and Public Administration, 2024)
This essay explores the dynamic interplay between migration, state control, and urban expansion in Shenzhen’s urban villages. With Shenzhen’s designation as a special economic zone in 1978, the city experienced unprecedented economic and demographic growth, primarily driven by rural-to-urban migration and facilitated by the government’s reform policies. This influx has led to the proliferation of urban villages, which are informal housing areas that have developed due to rapid urbanization and the state’s uneven regulatory oversight. These urban villages have become focal points of social and economic activity, housing diverse populations including migrant workers and local entrepreneurs. The essay argues that migration and state control are crucial in shaping the urban landscape of Shenzhen, influencing the development and characteristics of urban villages. Through a detailed examination of these areas, the essay highlights the complexities of urban expansion in the context of China’s broader socio-economic transformations.